Global Interactions in English as a Lingua Franca. How Written Communication is Changing under the Influence of Electronic Media and New Contexts of Use Franca Poppi. Bern: Peter Lang, 2012. 249 pages. ISBN: 978-3-0343- 1276-9 - Carmen Pérez Sabater (Ibérica, 2015)
.